Regulation of Justice in the Statute of Autonomy of Catalonia: Special reference to Judgment Spanish Constitutional Court 31/2010, of 28 june - Villanueva Turnes, Alejandro (Revista de Estudios de la Justicia, 2016)
This work has the objective of analysing of part of Statute of Autonomy of Catalonia relating to the Judicial Authority. To reach this objective will be analysed the different precepts and the jurisprudence that exist about them. It should be noted that the prosecution of Statute of Autonomy of Catalonia by the Constitutional Court Is considered by many such as trigger of the present situation in this Autonomous Community. All this implies that the analysis on this part of the Statute of Autonomy is a one thing really interesting today.